KONTROVERSI PEMBATASAN MASA JABATAN PRESIDEN DALAM PERSPEKTIF HUKUM TATA NEGARA - Muhammad Mas Davit Herman Rudiyansah (LPPM Universitas Nias Raya, 2025)
Presidential term limits are an important effort to maintain the balance of power and prevent abuse of power in the Indonesian government system. From a constitutional law perspective, these limitations are designed to avoid authoritarianism by ensuring a rotation of leadership that can bring about reform. However, presidential term limits have also raised controversy related to the principle of popular sovereignty, where the people have the right to choose a leader without limitations that are considered to limit their freedom. This study examines presidential term limits from the perspective of constitutional law and popular sovereignty, and analyzes their implications for political stability and people's rights in Indonesia's democratic system. Using normative legal methods, this study provides a comprehensive picture of the relevance of presidential term limits in maintaining a just democracy in Indonesia.